Moral Education Values in the Qur'an Recitation at the Bolo District, Bima Regency Marriage Ceremony - Nur hidayah; Muhammad Yaumi; Andi Achruh (Universitas Muhammadiyah Makassar, 2023)
ABSTRACTTitle : Moral Education Values in the Qur'an Recitation at the Bolo District, Bima Regency Marriage CeremonyThe objectives of this study were to 1) explain and analyze the role of moral education values in memorizing al-Qur'an recitations during wedding ceremonies in the Bolo community of Bima Regency. 2) to elaborate on the practice of memorizing Qur'an recitations during community wedding ceremonies. Bolo is located in the Bima Regency.This was a qualitative study that took a phenomenological approach through the use of interdisciplinary approaches such as pedagogical, psychological, and normative perspectives. These diverse approaches were capable of explaining the importance of moral education in memorizing the Qur'an recitations at the Bolo community's wedding ceremony, ranging from the importance of moral education, descriptions of memorizing recitations, etiquette in memorizing al-Qur'an recitations, fluency, to the relationship between memorizing and memorizing. recitation in conjunction with marriage.The study's findings indicated that while the reality of moral education values in memorizing al-Qur'an recitations was observed in the people of Bolo District, Bima Regency, particularly those related to memorizing al-Qur'an recitations, they needed to be improved and implemented optimally. As for the value of moral education in memorizing al-Qur'an recitations in the community of Bolo District, Bima Regency, it could be seen from the perspective of faith; exemplary could also be seen in the community's use of time; the community's empathy was quite good, even if some were found to be indifferent; however, sustainable development was required; however, when viewed from the perspective of responsibility, it was quite good, because it was quite v The description of memorizing the Qur'an recitations can be seen in two things that the community believes: To begin, memorizing served as a preventative measure against negative events, as it aided in the development and control of the community, requiring constant interaction and an understanding of the Qur'an's value. Second, as the source of Allah's mercy, as it contained an assembly of the Qur'an. Additionally, adab in recitations can be viewed from two perspectives: etiquette regarding reading and etiquette regarding dress in recitations. It was excellent in terms of fluency. The connection between memorizing recitations and marriage can be explained in three ways: first, it was believed to be a blessing; second, it was the hope of becoming a Qur'anic family; and third, it was the desire to become a Qur'anic family. Third, a social culture that had developed into a habit that necessitated activity.This research implied that various forms of Qur'an recitation activities that benefited moral education values and were carried out by the people of Bolo District, Bima Regency, should have been evaluated as efforts / constructive input in a memorizing activity. recitation of the Qur'an during the Bolo District's wedding ceremony. The evaluation included all stakeholders, including the government, parents, and society. Additionally, with various activities coupled with Qur'an recitations in the community of Bolo District, Bima Regency as indigenous wisdom and culture infused with religious values, the activities associated with weddings and other events should be developed and improved. in a variety of activities, both social and religious, which, of course, adds its value and unique style to moral values that are necessary throughout the ages. Keywords: Moral Education Value, Haflah Tilawah and Marriage.